Magneto-transport evidence for strong topological insulator phase in ZrTe5 - Jingyue Wang (Nature Portfolio, 2021)
It remains difficult to identify non-trivial band topology through electronic transport in narrow-gap topological materials. Here, the authors demonstrate that an inverted band leads to a four-fold splitting of non-zero Landau levels and an anomalous zero Landau level peak in the density of states of ZrTe5, hence can serve as an indicator to explore non-trivial topology.